Are Non-Eligible Students Affected by Special Education? - Jon Marius Vaag Iversen; Hans Bonesrønning; Ivar Pettersen (Center for Economic Studies and ifo Institute (CESifo), 2013)
We investigate whether the academic performance of non-eligible students - in an institutional setting of full inclusion - are affected by special education resources. Special education resources are per definition provided in a compensatory manner, and are increasingly being targeted to misbehaving students. The hypothesis is thus that special education resources might dampen the negative externalities associated with misbehaving students, and thus work to improve the performance of non-eligible students. We take advantage of a large, across-the-board increase in the proportion of eligible students, and combine fixed effects with an IV-approach, to identify the causal effects of special education on the academic performance of non-eligible students. We find that non-eligible students are positively affected by an increase in the number of hours in special education per eligible student.
Keywords: I20; I28; H52; 330; student achievement; special education; externalities